2018
DOI: 10.1007/s00270-018-1877-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Experience with Real-Time 3-D Guidance Based on C-Arm-Acquired Cone-Beam CT (CBCT) in Transjugular Intrahepatic Portosystemic Stent Shunt (TIPSS) Placement

Abstract: Real-time 3-D needle guidance based on CBCT is feasible for TIPSS placement. In terms of puncture attempts, duration and dose, CBCT guidance was not inferior to the control groups and may be a valuable support for interventionists in TIPSS procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 22 publications
3
19
3
Order By: Relevance
“…This is clearly less than the most recent reference DAP of 446.00 Gy cm 2 for TIPS procedures in the U.S. [31]. In detail, the DAP in our study is 30-80% lower than the mean DAPs reported in five studies using registration-guided TIPS procedures that range from 144.2 to 563.00 Gy cm 2 [12,[19][20][21][22][23][24] (s. Table 2). The difference between our median DAP of 61.14 Gy cm 2 to the lowest DAP for CACT-assisted TIPS procedures of 90.75 Gy cm 2 reported by Tacher et al might best be explained with the additional radiation exposure of the CACT reported to range from 18.00 to 63.90 Gy cm 2 [12,21,23].…”
Section: Discussioncontrasting
confidence: 72%
See 4 more Smart Citations
“…This is clearly less than the most recent reference DAP of 446.00 Gy cm 2 for TIPS procedures in the U.S. [31]. In detail, the DAP in our study is 30-80% lower than the mean DAPs reported in five studies using registration-guided TIPS procedures that range from 144.2 to 563.00 Gy cm 2 [12,[19][20][21][22][23][24] (s. Table 2). The difference between our median DAP of 61.14 Gy cm 2 to the lowest DAP for CACT-assisted TIPS procedures of 90.75 Gy cm 2 reported by Tacher et al might best be explained with the additional radiation exposure of the CACT reported to range from 18.00 to 63.90 Gy cm 2 [12,21,23].…”
Section: Discussioncontrasting
confidence: 72%
“…Therefore, 3D/2D image registered 3D-VM facilitates catheterization of the appropriate hepatic vein followed by successful 3D-guided puncture the portal vein, the most challenging step of TIPS procedures. The demographics of our study population and the indications for TIPS placement are comparable to the recent literature on 3D-guided TIPS procedures [12,[19][20][21][22] except for the studies by Luo et al, who included younger patients with refractory bleeding [23,24]. In our study, the TIPS placement under guidance of the 3D/2D image registered 3D-VM was successfully performed in all cases with a significant reduction of the PSG.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations